Fostering Religious Tolerance Through Quranic Education (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This study examines the potential of Quranic education in promoting religious tolerance and interfaith harmony. It analyzes key Quranic teachings on human equality, respect for diversity, and freedom of religion, and explores how these principles can be integrated into educational curricula. The research investigates practical strategies for implementing tolerance-focused Quranic education, including the development of inclusive curricula, promotion of interfaith dialogue, teacher training, and community empowerment. Using a qualitative approach based on literature review and content analysis, this study contributes to the ongoing discourse on religious education and its role in cultivating peaceful coexistence in diverse societies. The findings suggest that Quranic education, when properly implemented with a focus on its teachings of tolerance, can serve as an effective tool for building religious tolerance and promoting interfaith harmony.
Keywords: Quranic education; religious tolerance; interfaith dialogue; Islamic principles; educational strategies; curriculum development